IoT System Design of Thermoelectric Generator for Harvesting Motorcycle Exhaust Heat Energy - Ali K.; Mohamad A.J.; Rifai D.; Besar M.B.; Ikhmal M.A.; Mamat N.H.; Raja Aris R.S.N.A.; Siaw Paw J.K.; Abdalla A.N. (Springer Science and Business Media Deutschland GmbH, 2023)
Cellular telephones; Digital storage; Energy harvesting; Motorcycles; Secondary batteries; Thermoelectric equipment; Battery storage; Cellular Phone; Data access; Exhaust; Exhaust heat; Food delivery; Heat; Heat energy; Thermoelectric; Thermoelectric generators; Internet of things